Tumor necrosis factor alpha maintains denervation-induced homeostatic synaptic plasticity of mouse dentate granule cells - Becker, Denise; Zahn, Nadine; Deller, Thomas; Vlachos, Andreas (Frontiers in Cellular Neuroscience, 2013)
Neurons which lose part of their input respond with a compensatory increase in excitatory synaptic strength. This observation is of particular interest in the context of neurological diseases, which are accompanied by the loss of neurons and subsequent denervation of connected brain regions. However, while the cellular and molecular mechanisms of pharmacologically induced homeostatic synaptic plasticity have been identified to a certain degree, denervation-induced homeostatic synaptic plasticity remains not well understood. Here, we employed the entorhinal denervation in vitro model to study the role of tumor necrosis factor alpha (TNFα) on changes in excitatory synaptic strength of mouse dentate granule cells following partial deafferentation. Our experiments disclose that TNFα is required for the maintenance of a compensatory increase in excitatory synaptic strength at 3–4 days post lesion (dpl), but not for the induction of synaptic scaling at 1–2 dpl. Furthermore, laser capture microdissection combined with quantitative PCR demonstrates an increase in TNFα-mRNA levels in the denervated zone, which is consistent with our previous finding on a local, i.e., layer-specific increase in excitatory synaptic strength at 3–4 dpl. Immunostainings for the glial fibrillary acidic protein and TNFα suggest that astrocytes are a source of TNFα in our experimental setting. We conclude that TNFα-signaling is a major regulatory system that aims at maintaining the homeostatic synaptic response of denervated neurons.